Reforming for Racial Justice: A Narrative Synthesis and Critique of the Literature on District Reform in Ontario Over 25 Years - Shah, Vidya; Cuglievan-Mindreau, Gisele; Flessa, Joseph (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
Ontario school districts are struggling to respond to racism in schooling and society. How has the literature on school district reform in Ontario addressed these ongoing and growing concerns? Through a narrative synthesis and a systematic literature review, we map and characterize the existing literature on school district reform in Ontario in the past 25 years. By combining systematic searches in main online databases with key journal and author search, we analyzed and coded a total of 95 documents. Framed through Critical Race Theory (CRT) and in conversation with recent studies on anti-racist district reforms in the United States, we conceptualize four approaches to district reform literature in Ontario: The Politics of Race Evasion, the Politics of Illusory Equity, the Politics of Representation and Recognition, and the Politics of Anti-Racist Resistance. The authors conclude with a commentary on the use of these conceptualizations in district operations and policies, as well as directions for future research. They also propose a potential fifth approach to district reform, The Politics of Regeneration.